2015
DOI: 10.1590/0100-69912015006006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of polytrauma patients with kidney injuries in a university hospital

Abstract: The surgical approach was preferred due to penetrating trauma mechanism. We achieved low rates of complications and deaths, and neither case could be directly related to kidney damage, and there were patients with multiple lesions. In this sample, we could not observe a direct relationship between kidney damage and complications, deaths or the type of conduct employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…Contrary to our study, where blunt trauma was the most common cause (89.7%) of renal trauma, in a study by Guareschi et al [14] in Brazil, the most frequent mechanism was penetrating trauma, which amounted to 84.8%. However, Voelzke and Leddy found that 84% of renal traumas in adults and 89% of pediatric renal trauma were a result of blunt trauma, and more than 50% of traumas were due to motor vehicle accidents [15].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our study, where blunt trauma was the most common cause (89.7%) of renal trauma, in a study by Guareschi et al [14] in Brazil, the most frequent mechanism was penetrating trauma, which amounted to 84.8%. However, Voelzke and Leddy found that 84% of renal traumas in adults and 89% of pediatric renal trauma were a result of blunt trauma, and more than 50% of traumas were due to motor vehicle accidents [15].…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of patients in our study (83.8%) were male, and a similar situation can be found in other renal trauma studies [5,6,8,[14][15][16]. The age at admission was 23.9 ± 0.6 years (range = 5-61 years), and adolescents (age range 11-20 years) were the largest age group (30 cases).…”
Section: Discussionsupporting
confidence: 87%
“…The most common mechanism of injury involving the kidney is blunt trauma associated frequently to high-velocity deceleration (90% of cases); whereas penetrating trauma (gunshot and stab wounds occur in 1.4–3.3% [5, 1618, 36]. However, these incidences depend on the geographic area of the world [37].…”
Section: Methodsmentioning
confidence: 99%
“…The rate of renal trauma in this study was broadly consistent with other international studies. For instance, the rate of renal injury in the study by McPhee et al (2015) in London was 1.9% (12), in the study by Khoschnau et al (2020) in Qatar, 2.4% (4), and in the study by Guareschi et al (2015) in Brazil, it was 4.15% (20).…”
Section: Discussionmentioning
confidence: 83%